2015
DOI: 10.1016/j.agee.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Pollination services from field-scale agricultural diversification may be context-dependent

Abstract: A B S T R A C TDiversification of field edges is widely used as a strategy to augment pollinator populations and, in turn, supplement crop pollination needs. Hedgerow plantings, a commonly applied field-scale diversification technique, have been shown to increase wild bee richness within edges and into crop fields; however, their effects on pollination services in mass-flowering, pollinator-dependent crops typical of large-scale commercial monocultures are less well-known. We evaluated the indirect contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 62 publications
(98 reference statements)
5
56
0
Order By: Relevance
“…While the strength of the nesting results indicates that sunflower bee nesting is likely not linked to irrigation method, additional evidence from future studies could help confirm this conclusion. We collected numbers and species of bees in our netted sample that were similar to those in other studies in sunflower in our study region (Greenleaf and Kremen 2006a; Sardiñas and Kremen 2015); this similarity suggests our findings on the relationship of foraging bees to irrigation type may be robust to the effects of small study size.…”
Section: Study Sample Sizesupporting
confidence: 70%
“…While the strength of the nesting results indicates that sunflower bee nesting is likely not linked to irrigation method, additional evidence from future studies could help confirm this conclusion. We collected numbers and species of bees in our netted sample that were similar to those in other studies in sunflower in our study region (Greenleaf and Kremen 2006a; Sardiñas and Kremen 2015); this similarity suggests our findings on the relationship of foraging bees to irrigation type may be robust to the effects of small study size.…”
Section: Study Sample Sizesupporting
confidence: 70%
“…The edaphic characteristics preferred by wild bees for nesting may be slow to respond to restoration efforts that do not directly target soil properties. For example, although hedgerows in our study were between 5 and 12 years post‐planting (Morandin & Kremen ; Sardiñas & Kremen ), this short time frame might not be sufficient to affect significant changes in soils in agricultural field edges. Thus, once edaphic conditions suitable for bee nesting are identified (such as with alkali bees; Stephen ), specific techniques aimed at creating such conditions may need to be implemented at restoration sites.…”
Section: Discussionmentioning
confidence: 93%
“…We visually estimated indicators of nest‐site quality within e‐traps following the work of Sardiñas and Kremen () and Potts et al (). We focused on indicators that have been found to significantly impact nesting rates: percent bare ground, variation of slope of the ground, surface soil compaction, and soil particle size (Table ; Sardiñas & Kremen ; Grundel et al ; Potts et al ).…”
Section: Methodsmentioning
confidence: 99%
“…The current results help to think in terms of flower sizes and densities in real systems and to interpret other studies in this light. For example, in a recent study wild bees were hardly found in sunflower field interiors [82], which may be a result of enough pollen being offered near the nest, explaining that the quality of the edge habitat did not have an effect on the pollinator community in the interior of the field [82]. Our model suggests that an increase in fragmentation and the ratio of nest to foraging habitat at a very local scale should increase pollinator coverage largely independent of flower size.…”
Section: Discussionmentioning
confidence: 99%